The Effect of Volume Fraction on Acoustic Properties of Areca Nut Midrib Fibers Composites with Natural Adhesives - Putri Pratiwi; Hendriwan Fahmi; Asmara Yanto; Idel Fitra Soni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
Areca nut Midrib is one of agricultural waste that has many benefits to be recycled for household purposes such as plates, jars and others. Moreover, for many researchers, areca nut midrib fiber was used as a filler of composites material. From several studies it is known that this material has good potential as filler in composites because of its good mechanical properties. In addition, this material is also considered as a good sound absorber. Therefore, this research will investigate the ability of sound absorption from this material in a various composition. We used Areca nut Midrib fibers as a filler and pine sap as a matrixof composite with a volume fraction of 70%: 30%, 75%: 25%, 80%: 20%, 85%: 15%, 90%: 10%. The sound absorption coefficient of composites was studied using impedance tube method with 500, 1000 Hz, 1500 Hz, 2000 Hz, and 2500 Hz frequency. The results showed that at a test frequency of 500 Hz, the value of sound absorption coefficient increases with the increase of Areca nut Midrib fraction. This research shown that there is an effect of volume fraction on the acoustic properties and Areca nut Midrib fiber composite have potential used as sound absorption materials, based on ISO standard 11654:1997.